2019
DOI: 10.1016/j.sjbs.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro antimicrobial and anticancer properties of green synthesized gold nanoparticles using Anacardium occidentale leaves extract

Abstract: The aqueous cashew leaves extract obtained was investigated for the preparation of gold nanoparticle (AuNPs). The obtained AuNPs were characterized by UV–Visible spectroscopy, FTIR and XRD analysis. Results indicated that the green synthesized AuNPs showed good antibacterial effect against Escherichia coli and Bacillus subtilis and exhibited 74.47% viability on PBMC and 23.56% viability on MCF-7 cell lines at a maximum concentration of 100 µg/ml. Therefore, future … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(53 citation statements)
references
References 36 publications
(43 reference statements)
3
42
0
3
Order By: Relevance
“…By increasing the amount of ROS, it disrupts the cell wall and membrane structure, causing damage to vital functions such as DNA, RNA synthesis, and affinity to ROS. [ 5,26 ] The antimicrobial activity of AuNPs synthesized with plant ( C. annuum green leaves) extract was investigated. It was determined that these particles have a strong antimicrobial effect at low concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…By increasing the amount of ROS, it disrupts the cell wall and membrane structure, causing damage to vital functions such as DNA, RNA synthesis, and affinity to ROS. [ 5,26 ] The antimicrobial activity of AuNPs synthesized with plant ( C. annuum green leaves) extract was investigated. It was determined that these particles have a strong antimicrobial effect at low concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…[ 28 ] In another study with Anacardium occidentale , it was reported that 20–40 mg mL −1 concentrations were effective on E. coli and B. subtilis . [ 26 ]…”
Section: Resultsmentioning
confidence: 99%
“…At the same time, most of the proposed NPs seemed to have a good efficiency against the various tumoral cells, with half maximal effective concentrations usually under 100 mg/L. For example, against breast adenocarcinoma cells (MCF-7), the best results in the MTT assay were achieved by using spherical silver nanoparticles that were obtained by using Tropaeolum majus L. leaf extracts (EC 50 = 2.49 mg/L) [24], followed by spherical gold nanoparticles that were obtained by using Anacardium occidentale L. leaves (EC 50 = 6 mg/L) [53]; the same types of NPs were also found to be efficient against human cervical epithelioid carcinoma cells (HeLa) (Ag NPs that were obtained by using Piper longum leaves-EC 50 = 5.27 mg/L [88] and Au NPs that were obtained by using Alternanthera sessilis leaves-EC 50 = 10 mg/L [99]), while the most effective nanoparticles against human lung carcinoma cells (A549) were proven to be silver NPs that were obtained by using Scorzonera calyculata aerial parts (EC 50 = 12.5 mg/L) [35], gold NPs that were obtained by using Marsdenia tenacissima leaves (EC 50 = 15 mg/L) [95], MgO NPs that were obtained by using Sargassum wightii (EC 50 = 37.5 mg/L) [70], and ZnO NPs that were obtained by using Allium cepa leaves (EC 50 = 51.25 mg/L) [66].…”
Section: Antitumoral Applicationsmentioning
confidence: 99%
“…Anticancer activity is the effect of natural, synthetic, or biological agents that suppress and prevent carcinogenic progression. Several synthetic agents plant-derived chemotherapeutic drugs are being used in the treatment of cancer (Sunderam et al, 2019). Oats contain more than 20 unique polyphenols, avenanthramides exhibiting anti-in lammatory, and anti-proliferative activity, which inhibits the progression of cancer (Meydani, 2009).…”
Section: Introductionmentioning
confidence: 99%